Social Semiotics of Low Multi-Purpose Vehicle (MPV) Car Ads in Indonesia - Yudhistiro Pandu Widhoyoko (Universitas Muhammadiyah Semarang, 2022)
The purpose of this study was to determine the verbal and non-verbal meanings as copywriting in car product advertisements in the low minivan or MPV class marketed in Indonesia in terms of semiotics. This research is a qualitative research with descriptive-analytical method with a focus on describing verbal and non-verbal meanings in car product advertisements in the low minivan or MPV class marketed in Indonesia. The data sources used in this thesis are Youtube channels with URLs; https://www.youtube.com/watch?v=11MDA0KR28s. The data used is the number of automotive product advertisements in the minivan or MPV class marketed in Indonesia. The seven car advertisements are Toyota Avanza 1500, Toyota Avanza Veloz, Suzuki Ertiga, Daihatsu Xenia, Honda Mobilio, Mitsubishi Expander, and Wuling Confero S. These seven advertisements are advertisements produced between 2018-2019.